Platelet-rich fibrin: Evolution of a second-generation platelet concentrate - Sunitha Raja V; Munirathnam Naidu E (Wolters Kluwer Medknow Publications, 2008)
Platelet-rich plasma (PRP) is a platelet concentrate that has been used widely to accelerate soft-tissue and hard-tissue healing. The preparation of PRP has been described by several authors. Platelet-rich fibrin (PRF) was first described by Choukroun et al. in France. It has been referred to as a second-generation platelet concentrate, which has been shown to have several advantages over traditionally prepared PRP. Its chief advantages include ease of preparation and lack of biochemical handling of blood, which makes this preparation strictly autologous. This article describes the evolution of this novel platelet concentrate, referred to as PRF.